Synthetic approaches to multifunctional indenes - Mesquida, Neus; López-Pérez, Sara; Dinarès, Immaculada; Alcalde, Ermitas (Beilstein Journal of Organic Chemistry, 2011)
The synthesis of multifunctional indenes with at least two different functional groups has not yet been extensively explored. Among the plausible synthetic routes to 3,5-disubstituted indenes bearing two different functional groups, such as the [3-(aminoethyl)inden-5-yl)]amines, a reasonable pathway involves the (5-nitro-3-indenyl)acetamides as key intermediates. Although several multistep synthetic approaches can be applied to obtain these advanced intermediates, we describe herein their preparation by an aldol-type reaction between 5-nitroindan-1-ones and the lithium salt of N,N-disubstituted acetamides, followed immediately by dehydration with acid. This classical condensation process, which is neither simple nor trivial despite its apparent directness, permits an efficient entry to a variety of indene-based molecular modules, which could be adapted to a range of functionalized indanones.
Keywords: aldol reaction; amides; indanones; indenes; organometallic reagents